EFFICIENCY INDICATORS OF COMMERCIAL BANKS IN LIBERALISED ENVIRONMENT IN INDIA - Nageshwar Rao and Shefali Tiwari (Abhigyan, 2009)
Globalization and capital market growth, combined with a shift of focus from interest income to more stable fee income, are placing bank's lending and deposit businesses under increasing pressure. Banks are paying more attention to their cash trade and treasury businesses. Thus, banks are concentrating more on micro and macro factors of efficiency. Falling interest rates, a pick up in demand for loans, chiefly in retail sector and good spreads in treasury transactions caused a substantial face lift to all players in the banking sector. All top rated bank have succeeded in reducing their NPA's by around 65 percent to 100 percent. The growth in business is also an impressive 24-41 percent. But, one thing that is sending alarm signals is that stronger banks are becoming stronger and weaker ones are in the process of being wiped off. This calls for an in depth study of efficiency in the banking sector, the factors responsible for success and failure of banks. This study would enable to identify efficiency factors affecting the banks individually as well as an industry. Prediction of the future performance of banks would be more accurate and hence reliable. This wiNageshwar Raoll again help in taking corrective measures and planning.